2022
DOI: 10.3389/fpubh.2022.783153
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence and Characteristics of Perinatal Stroke in Beijing: A Multicenter Study

Abstract: ObjectiveTo assess the incidence, risk factors, and clinical characteristics of perinatal stroke in Beijing.MethodsThis multicenter prospective study included all the live births from 17 representative maternal delivery hospitals in Beijing from March 1, 2019 to February 29, 2020. Neonates with a stroke were assigned to the study group. Clinical data, including general information, clinical manifestations, and risk factors, were collected. Up until 18 months after birth, neonates were routinely assessed accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…226 A multicenter prospective study in Beijing included all the live births from 17 representative maternal delivery hospitals from March 1, 2019, to February 29, 2020. 227 A total of 27 cases were identified, and the incidence of perinatal stroke in Beijing was 1 in 2660 live births, including 1 in 5985 for ischemic stroke and 1 in 4788 for hemorrhagic stroke.…”
Section: Stroke (Cerebrovascular Diseases)mentioning
confidence: 99%
See 1 more Smart Citation
“…226 A multicenter prospective study in Beijing included all the live births from 17 representative maternal delivery hospitals from March 1, 2019, to February 29, 2020. 227 A total of 27 cases were identified, and the incidence of perinatal stroke in Beijing was 1 in 2660 live births, including 1 in 5985 for ischemic stroke and 1 in 4788 for hemorrhagic stroke.…”
Section: Stroke (Cerebrovascular Diseases)mentioning
confidence: 99%
“…A multicenter prospective study in Beijing that included all the live births from 17 representative maternal delivery hospitals from March 1, 2019, to February 29, 2020, found that the risk factors include primiparity, placental or uterine abruption/acute chorioamnionitis, intrauterine distress, asphyxia, and severe infection. 227…”
Section: Stroke (Cerebrovascular Diseases)mentioning
confidence: 99%
“…Recent studies have focused on identifying inflammatory biomarker signatures in patients at-risk for perinatal stroke ( 41 ), which may improve the ability to detect perinatal stroke early and allow initiation of supportive therapies sooner. Some experts have recommended more widespread use of neuroimaging in neonates with risk factors for stroke ( 42 ), but clear algorithms are still lacking to define which neonates are at highest risk. Placental pathology may provide input into a stroke risk stratification algorithm, but the timeframe required for placental examination will be a limiting factor until new techniques are developed that can offer real-time, clinically-relevant information.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of perinatal stroke is estimated as high as one per 1100 live births [2], but lower rates have been reported [3][4][5][6]. Most estimates are based on small samples over short periods of time, with variable ascertainment methods.…”
Section: Incidencementioning
confidence: 99%
“…Infants with stroke typically present with seizures or other diffuse neurologic deficits. Some infants with stroke are not identified acutely, but are diagnosed retrospectively, when neurologic symptoms, such as emerging hemiparesis or seizures, leads to neuroimaging [ 5 ]. In contrast, children with stroke typically present with focal neurologic deficits, usually hemiplegia and/or focal seizures.…”
Section: Introductionmentioning
confidence: 99%